Secondary pollen presentation and foral traits of Heliconia psittacorum - Nascimento, Talita Oliveira; Silva, Patricia Campos; Loges, Vivian; Mariotto, Sandra; Krause, Willian; Silva, Celice Alexandre (Ornamental Horticulture, 2018)
The secondary presentation of pollen consists of a foral mechanism where the presentation of pollen occurs in other foral structures in addition to the anther, in order to increase the precision of the dispersion of the pollen by the vectors. This study aims to describe the temporal dynamics of secondary pollen presentation, and morphological and morphometric characteristics in stages of pre- anthesis and anthesis in genotypes of fve natural Heliconia psittacorum populations. For the study of foral morphometry traits of length of the fower, stamen, stigma and height of flament insertion in the petal in bud and fower were measured. The foral morphology of pre-anthesis buds and fowers in anthesis, the presence or absence of characteristics such as herkogamy, region of flament insertion in the petal, region of stylar hairs, and of secondary pollen deposition were evaluated. Treatments of controlled pollinations, self-pollination, geitonogamy, cross-pollination, natural pollination and growth to pollen tube were sampled. Floral herkogamy and pollen transfer to the adhered hairs in the stylar region were clearly observed during anthesis, constituting the frst record of occurrence of secondary pollen presentation in Heliconiaceae. Pollen tube growth was inhibited in the stigmatic, style and basal regions of the pistil. Natural fruiting produced little or no fruit. The positioning of the stamens above the stigma, pollen viability and stigma receptivity during anthesis of H. psittacorum fowers may favor self-pollination. The stylar hairs observed in all H. psittacorum populations’ help in the retention of pollen grains. The low fruiting rate in controlled and natural pollinations suggest that the main propagation form of H. psittacorum in the study areas is based on asexual reproduction.